2010
DOI: 10.1002/jgm.1506
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid herpes simplex virus/Epstein–Barr virus amplicon viral vectors confer enhanced transgene expression in primary human tumors and human bone marrow‐derived mesenchymal stem cells

Abstract: Taken together, we have demonstrated that these hybrid vectors could be promising tools as carriers of therapeutic genes in mesenchymal stem cells or even provide an alternative non-integrating platform for the generation of induced pluripotent stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Hybridized EBNA-1 elements of the EBV vector with herpes simplex virus type-1 (HSV-1) have shown high vector levels and prolonged transgene expression. EBNA-based episome may represent an alternative nonintegrating platform for anticancer-engineered MSC therapy [51].…”
Section: Transfection Methodsmentioning
confidence: 99%
“…Hybridized EBNA-1 elements of the EBV vector with herpes simplex virus type-1 (HSV-1) have shown high vector levels and prolonged transgene expression. EBNA-based episome may represent an alternative nonintegrating platform for anticancer-engineered MSC therapy [51].…”
Section: Transfection Methodsmentioning
confidence: 99%
“…This is because the transgene expression can only be sustained up to a maximum of 14 days due to the nonintegrating nature of the HSV-1 virions [25]. We have recently generated a HSV/Epstein Barr virus (EBV) hybrid vector and showed stable luciferase gene expression in the mouse brain for up to 1 year [53]. Thus, to improve the stability, the pHGCX-TRAIL construct can be subcloned into the HSV/EBV hybrid vector for stable gene expression.…”
mentioning
confidence: 99%
“…Enhanced efficacy has also been shown by the fusion of yCD to the HSV-1 tegument protein (VP22), which increases the spread of the fusion proteins to surrounding recipient cells. 45,46 Besides the genetic manipulation of the therapeutic gene, one can also improve on the stability of the viral vectors by the incorporation of nonintegrating episomal elements such as the EBNA-1/oriP system, 47,48 or the employment of a replication-competent HSV-1 viruses. Nakamura et al 49 demonstrated that such a mutant virus that expressed the yCD had greater therapeutic effect than the oncolysis induced by the viral replication alone.…”
Section: Discussionmentioning
confidence: 99%
“…Whole cellular DNA was extracted using the QIAamp DNA mini kit (Qiagen) according to the manufacturer's instruction with RNase treatment. The DNA samples were then subjected to quantitative PCR analysis to determine the vector genome copy number as described previously 47 using a Rotor-Gene Q real-time PCR system (Qiagen) with QuantiTect SYBR Green PCR Kit (Qiagen).…”
Section: Vector Genome Copy Number Analysismentioning
confidence: 99%
See 1 more Smart Citation